2007
DOI: 10.2463/mrms.6.249
|View full text |Cite
|
Sign up to set email alerts
|

MR Virtual Endoscopy for Biliary Tract and Pancreatic Duct

Abstract: Developments in magnetic resonance (MR) equipment and techniques have been remarkable. Especially, respiratory-triggered three-dimensional MR cholangiopancreatography (3D-MRCP) has been developed to provide images with high spatial resolution of the biliary tract and pancreatic duct. These 3D data can be employed in MR virtual endoscopy (MRVE) with volume rendering to visualize the lumina of the gallbladder, bile duct, and pancreatic duct. To observe the changes in the lumina with threshold settings on a works… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The virtual MR endoscopic technique is used to gain an image display by the processing of 3D data sets to provide a simulated visualization of a patient's hollow organs similar to that produced by using standard endoscopes; meanwhile, the total processing was not time-consuming [10]. Studies have described clinical applications of virtual endoscopy to visualize the inside of the cerebellopontine angle [11], shoulder [12], biliary tract and pancreatic duct [13], and urinary tract [14]. To our knowledge, there is no large series in the literature related to virtual MR endoscopy application in the fetus [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The virtual MR endoscopic technique is used to gain an image display by the processing of 3D data sets to provide a simulated visualization of a patient's hollow organs similar to that produced by using standard endoscopes; meanwhile, the total processing was not time-consuming [10]. Studies have described clinical applications of virtual endoscopy to visualize the inside of the cerebellopontine angle [11], shoulder [12], biliary tract and pancreatic duct [13], and urinary tract [14]. To our knowledge, there is no large series in the literature related to virtual MR endoscopy application in the fetus [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have indicated that it has contributed to shortening the procedure time, improving the procedure success rate, and reducing the incidence of complications. Respiratorytriggered three-dimensional MR cholangiopancreatography (3D-MRCP) provides high-spatial-resolution images of the biliary tract and pancreatic duct, and enables MR virtual endoscopy using volume rendering to visualize the lumens of the gallbladder, bile duct, and pancreatic duct [6]. However, the utility of 3D-CT image in ERCPrelated procedures has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have described clinical applications of virtual endoscopy to visualize the inside of the bronchi, paranasal sinus, stomach, bladder, small intestine, pancreatic duct, bile duct, and spine (2,6,8,10,11,16,19,21,23,24). Shigematsu et al (20) reported the use of virtual intravascular MR endoscopy for aneurysms in three cases.…”
Section: Incesu L Et Al: Mr Endoscopy In Cerebral Aneurysmsmentioning
confidence: 99%
“…Studies have described clinical applications of virtual endoscopy to visualize the inside of the tracheobronchial tree, paranasal sinus, stomach, bladder, small intestine, pancreatic duct, bile duct, and spine (2,(6)(7)(8)10,11,16,19,21,23,24). Virtual endoscopy used for preoperative planning in neurosurgery for endoscopic third ventriculostomy, nasal cavity and paranasal sinus surgery, and virtual endoscopy visualization of the sphenoid sinus and important adjacent structures is valuable for training and the preoperative planning of endonasal transsphenoidal surgery (15).…”
Section: Incesu L Et Al: Mr Endoscopy In Cerebral Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation